AN ANALYSIS OF ILLOCUTIONARY AND PERLOCUTIONARY SPEECH ACTS OF AN INSTAGRAM ONLINE SHOPPING ACCOUNT - Cahya Wati Dewi (PROJECT (Professional Journal of English Education), 2021)
Language is important in human’s life because we cannot communicate with one another without it. Therefore, it is appealing to study speech acts since we can understand how utterances are reflected in actions. It is also interesting to analyze the speech acts used in Instagram captions. This study aims to analyze speech acts of an online shopping account on Instagram that is an international brand N.Y.X. Illocutionary speech acts aims to state something to influence the listener to do activities according to what the speaker means. Based on the data obtained, the illocutionary act of the online shopping account @nyxcosmetics is in the form of directive and expressive acts. The directives illocution acts are ordering and demanding. On the other hand, the perlocutionary aims to portray the act of offering someone. Keywords: Speech acts, Illocutionary acts, Perlocutionary acts